Improving the Students' Listening Skill by using Shadowing Technique - Binarkaheni, Suyik; Dewangga, Vigo (Journal of English in Academic and Professional Communication, 2024)
This study aimed to observe of implementation of the shadowing to improve students’ listening skills. The subjects were one group out of 3 groups of first-semester Poultry students Department of Polytechnic Jember, which consisted of 20 students. This study was conducted by using action research and experimental research. The observation and diary notes were employed to collect the data for action research. Listening tests were employed to collect the data for the experimental research. This research is cyclical research which is divided into 2 cycles. Each cycle has 4 stages, they were planning, implementation, observation, and reflection. The results of the listening test showed there was students’ listening skills improved after the completion of the shadowing method, which is shown by the mean scores of 58,55 and 84,6 at the end of the cycle. Based on the observation and diary notes showed the pleasure, enthusiasm, and motivation of the students to learn English at a high level. As a result, it could be summarized that the shadowing method could be used to improve the students’ listening skills.